Pharmacognostical and phytochemical studies on roots of Bombax ceiba Linn. - Pankaj H. Chaudhary; Pallavi D. Rai; Sharada L. Deore; Somshekhar S. Khadabadi (GarVal Editorial Ltda., 2014)
Context: Bombax ceiba Linn. (Bombacaceae) is a well-known plant for its antihypertensive, antioxidant, antidiabetic, aphrodisiac and uterine tonicity properties. Aims: To study pharmacognostical, physicochemical and phytochemically the roots of this plant. Methods: Pharmacognostical study included the macroscopic characters like size, color, surface characteristics, texture, fracture characteristics and odor of the roots. The intact root as well as powdered drug were studied under a microscope to analyze the cellular characteristics of the drug. Physicochemical parameter like extractive values, loss on drying (LOD), total ash, water-soluble and acid insoluble ash, foaming index and hemolytic index of Bombax ceiba root powder were determined as per WHO guidelines. Preliminary phytochemical screening and qualitative chemical examination studies have been carried out for the various phytoconstituents. HPTLC have also carried out using cyclohexane: diethyl ether: ethyl acetate as mobile phase. Results: Chemical evaluation and TLC studies shown presence of alkaloids, glycosides, flavonoids, steroids, saponins and tannins. The microscopic characters have shown presence of cork, cambium, xylem vessels, stone cells, starch grains, calcium oxalate crystals and phloem fibers. Microscopy analysis of the powder included the cork cells, fibers, calcium oxalate crystals and vessel. The presence of steroids was confirmed in HPTLC fingerprinting studies. Conclusions: Pharmacognostical and preliminary phytochemical screening of Bombax ceiba roots will be useful in order to authenticate, standardize and avoid any adulteration in the raw material. The diagnostic microscopic characters and physicochemical data will be helpful in the development of a monograph. The chromatographic fingerprinting profile can be used to standardize extracts and formulations containing Bombax ceiba roots.